MERGER STRATEGY OF SHARIA BANKS INTO BSI: INCREASING MARKET SHARE OF SHARIA ECONOMY - rostiani, helda helda; JUNAIDIN , JUNAIDIN; A. GUSTANG , A. GUSTANG (Islamic Economic and Business Journal, 2025)
The purpose of this study is to increase the market share of Islamic finance in Indonesia, the Ministry of BUMN merged three BUMN Islamic banks, BNI Syariah, BRI Syariah, and BRI Syariah. and the transformation of Bank Syariah Mandiri into Bank Syariah Indonesia (BSI) to expand the Islamic banking market, which is the driving force of Islamic finance in Indonesia. The qualitative approach in desk research emphasizes the collection of secondary data such as research results, books, news, magazines, journals, and other references. economic development that adheres to sharia principles in Indonesia. This study investigates how the merger of state-owned Islamic banks increased market share. The results show that increasing the market share of Islamic finance is the goal of the merger strategy in state-owned Islamic banks. One of the advantages of Indonesian sharia is as follows: (a) superior local and regional knowledge that can improve the efficiency of financial transactions; (b) large capital assets combined with diverse product innovations that result in high sharia-based funding, stable liabilities, and impressive profitability; and (c) professionalism and system-supported, technological sophistication, and robust service features that distinguish sharia transactions from others.